Inland view of the Flats - Branch Cultural Historical Association (2008)
The Flats provide a considerable tract of agricultural land in Branch. Suitable for growing vegetables and a source of hay, the Flats also provide livestock pasturage. In his book Sport, Travel and Adventure in Newfoundland and the West Indies, Captain Kennedy wrote of his visit to Branch in the late-1800s, The village was picturesquely situated in a valley, and presented a very pleasing and well-to-do appearance, quite in contrast to the generality of Newfoundland settlements; this was due to the fact that the valley afforded pasturage to herds of cattle and sheep, and a considerable part of it was devoted to agriculture. I never saw finer potatoes, or better cream, bread, butter, or fatter poultry or stock, in any place than at Branch River, showing what can be done by perseverance. The hay crops were magnificent, and the whole place bore the aspect of a well-to-do farm in the Lowlands of Scotland. It is certainly the most flourishing little place in Newfoundland. -- Sport, Travel and Adventure in Newfoundland and the West Indies, 1885, Captain W. R. Kennedy